1996
DOI: 10.1021/jo952285h
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Synthesis of (−)-Mirabazole C Using a Chloroimidazolidium Coupling Reagent, CIP

Abstract: Convergent synthesis of (−)-mirabazole C (1), a tetra thiazoline/thiazole alkaloid isolated from blue-green alga, has been described. The successive thiazoline rings of (−)-mirabazole C were formed by a single-step cyclization mediated by TiCl4 treatment of tripeptide amide 4. Convergent synthesis of the key intermediate 33 derived from three 2-methylcysteine residues was first achieved using a newly developed coupling reagent, 2-chloro-1,3-dimethylimidazolidium hexafluorophosphate (CIP). The effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Carpino's HATU reagent (Chart ) also gives excellent results for Aib couplings and has the advantage over the amino acid fluorides of being commercially available and enabling one-pot coupling protocols. HATU permits the linkage of adjacent Aib residues in quantitative yield, whereas HOBt protocols give less than satisfactory results. , Another similarly based method is CIP (Chart ) in the presence of additive HOAt, which mediates solution phase Aib couplings in good to excellent yield (82−90% for Z-Aib-Aib-OMe). , The yields for these couplings in the absence of HOAt were comparable with those obtained from PyBrop (10−60%), but the additive HOAt improved them dramatically …”
Section: αα-Disubstituted and Other Hindered Residuesmentioning
confidence: 99%
“…Carpino's HATU reagent (Chart ) also gives excellent results for Aib couplings and has the advantage over the amino acid fluorides of being commercially available and enabling one-pot coupling protocols. HATU permits the linkage of adjacent Aib residues in quantitative yield, whereas HOBt protocols give less than satisfactory results. , Another similarly based method is CIP (Chart ) in the presence of additive HOAt, which mediates solution phase Aib couplings in good to excellent yield (82−90% for Z-Aib-Aib-OMe). , The yields for these couplings in the absence of HOAt were comparable with those obtained from PyBrop (10−60%), but the additive HOAt improved them dramatically …”
Section: αα-Disubstituted and Other Hindered Residuesmentioning
confidence: 99%
“…The excess reagent was removed by evaporation under a stream of Ar gas. The resulting slurry was dissolved in CH 2 Cl 2 , filtered through a cotton plug, and subjected to GC on an L‐Val‐coated capillary CHROMPACK™ column . The sample was eluted with a temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it has been reported that in the synthesis of analogs of mosapride [329] CDI was more efficient than 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide (EDC). The imidazolium reagent BOI 74 and its precursor CIP 75 were developed by Kisos group [331]. The imidazolium reagent BOI 74 and its precursor CIP 75 were developed by Kisos group [331].…”
Section: Further Special Methods For Peptide Synthesismentioning
confidence: 99%